Russian Federation Financial Sector Assessment Program : Macroprudential Policy - International Monetary Fund (Washington, DC, 2017)
Financial stability oversight responsibilities are currently shared between the Central Bank of Russia (CBR) and a high-level inter-agency National Council on Ensuring Financial Stability (FSC). Given its role as the single financial regulator and supervisor since September 2013, CBR has naturally become a macroprudential authority. In recent years, CBR has used a number of macroprudential tools to deal with risks, mainly those stemming from retail lending. An expanded use of macroprudential tools to establish adequate buffers could help safeguard financial stability in the medium term. The economy is highly exposed to swings in oil prices, which in turn may significantly affect financial conditions and amplify business cycles through macrofinancial linkages. In the medium term, greater volatility driven by oil price movements may warrant a larger buildup of buffers to protect banks against solvency risk. The CBR Law should be amended to provide for a more comprehensive set of macroprudential tools. Currently, the law does not provide a legal foundation for CBR to use the full set of recognized macroprudential tools, such as limits on loan-to-value (LTV) and debt service-to-income (DSTI) ratios, as well as on growth of certain credit. The current institutional arrangements appear to be functioning well, but some additional steps could be taken to support timely macroprudential actions in the future. CBR has the necessary technical capacity for systemic risk monitoring and assessment, but additional work is needed. CBR regularly publishes Financial Stability Review, which is indicative of strong analytical capacity.